Effectiveness and safety of secukinumab in axial spondyloarthritis: a 24-month prospective, multicenter real-life study. (April 2022) - Ramonda, Roberta; Lorenzin, Mariagrazia; Sole Chimenti, Maria; D'Angelo, Salvatore; Marchesoni, Antonio; Salvarani, Carlo; Lubrano, Ennio; Costa, Luisa; Dal Bosco, Ylenia; Fracassi, Elena; Ortolan, Augusta; Ferraioli, Mario; et al.
Objectives: To evaluate, in a multicentric Italian cohort of axial spondyloarthritis (axSpA) patients on Secukinumab (SEC) followed for 24 months: (1) the long-term effectiveness and safety of SEC; (2) the drug retention rate and low disease activity (LDA) measured as Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) < 4/Ankylosing Spondylitis Disease Activity Score (ASDAS) < 2.1 and very low disease activity (VLDA) measured as BASDAI < 2/ASDAS < 1.3; (3) any differences in outcomes according to line of biological treatment (naïve/non-naïve), gender (male/female), subtype of axSpA [radiographic axSpA (r-axSpA)/non-radiographic axSpA (nr-axSpA)]. Methods: Consecutive axSpA patients treated with SEC were evaluated prospectively. Disease characteristics, previous/ongoing treatments, comorbidities, and follow-up duration were collected. Disease activity/functional/clinimetric scores and biochemical-values were recorded at baseline (T0), 6 (T6), 12 (T12), and 24 (T24) months. Effectiveness was evaluated over-time with descriptive statistics; multivariate Cox and logistic regression models were used to evaluate predictors of drug discontinuation and LDA at T6. Infections and adverse events were recorded. Results: A total 249 patients (47.8% male; median age 51) were enrolled; 40.9% had HLA-B27; 53.8% had r-axSpA, and 46.2% nr-axSpA. SEC was prescribed in 28.9% naïve and in 71.1% non-naïve patients. SEC effectiveness was shown as an improvement in several outcomes, such as ASDAS [T0 = 3.5 (2.9–4.4) versus T24 = 1.9 (1.2–2.4); p = 0.02] and BASDAI [T0 = 6.5 (5.0–7.5) versus T24 = 2.8 (1.8–4.0); p = 0.03]. At T24, naïve patients showed better physical functioning and lower disease activity than non-naïve. After 24 months of treatment, 90.7% of naïve and 75.3% of non-naïve patients achieved LDA (BASDAI < 4). Treatment was discontinued in 24.5% patients, mainly due to primary/secondary loss of effectiveness, and in 6.8% due to adverse events. Retention rate at T24 was 75% in the whole population, with some difference depending on gender ( p = 0.002). Conclusion: In a real-life clinical setting, SEC proved to be safe and effective in axSpA, mainly in naïve-patients, with a notable drug retention rate. No differences were observed between r-axSpA and nr-axSpA.